A171 FACTORS OF SOCIAL PARTICIPATION IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE. (4th March 2021) - Su, S; Marrie, R; Bernstein, C N
Abstract: Background: Inflammatory bowel disease (IBD) including Crohn's disease (CD) and ulcerative colitis (UC) imposes a significant burden on health-related quality of life, particularly in social domains. We sought to investigate the factors that limit social participation in patients with IBD. Aims: Our first aim was to identify if active IBD symptoms had an effect on an objective measure of social participation. Our secondary aim was to determine if psychiatric comorbidity and/or active psychiatric symptoms in IBD patients had an influence on social participation. Methods: We assessed a cohort of 239 Manitobans with IBD. We collected sociodemographic information, medical comorbidities, disease phenotype, symptom activity and psychiatric comorbidity (using the Structured Clinical Interview for DSM-IV). Participants completed the 8-item Ability to Participate in Social Roles and Activities questionnaire, which assesses participation restriction, including problems experienced in social interaction, employment, transportation, community, social, and civic life. Results: Poorer social participation score were associated with earning less than average income (p<0.001), being unemployed (p<0.001), actively smoking (p=0.006), higher symptom scores, and having an increasing number of chronic medical conditions (R= -0.296). History of depression (p<0.001) and anxiety (p=0.001) and having active depression (p<0.001) and anxiety (p=0.001) all predicted poor social participation scores. Patient's with UC on 5-ASA (PO/PR) seem to have higher social participation than other therapies. Phenotype was not predictive. Based on multivariate linear regression analysis, 38.8% of variability in social participation was explained by medical comorbidity, psychiatric comorbidity, psychiatric symptoms, and IBD related symptoms. Conclusions: The factors that predict social participation by IBD patients include income, employment, smoking, medical comorbidities, IBD symptom burden, and psychiatric comorbidities. Multivariate linear regression suggests that the most relevant factors are medical comorbidity, psychiatric comorbidity, psychiatric symptoms, and IBD symptoms. Funding Agencies: CIHRCrohn's and Colitis Canada